Non-Adherence to Anti-Hypertensive Treatment - ., Shalini; Goel, Manish Kumar (Indian Journal of Community Health, 2020)
Background: In developed countries, adherence among patients suffering from chronic diseases averages only 50%; in developing countries it is assumed to be much lower. Aims & objectives: To find out the prevalence of non-adherence to antihypertensive treatment among individuals seeking anti-hypertensive treatment from tertiary care hospital in New Delhi & to find out the factors related to non-adherence to the anti-hypertensive treatment among study subjects. Material and Methods: A cross-sectional hospital-based study was conducted from June to October 2018 among 150 diagnosed cases of hypertension. The drug adherence was assessed by using standard Brief Medication Questionnaire I (BMQ I) and to know the determinants of non-adherence a semi-structured (self-designed and pre tested) questionnaire was used. The association of different factors with adherence was analyzed by applying chi square (?2) test. Results: Among total of 150 participants 44% were males and 56% were females. The magnitude of non-adherence to anti-hypertensive drugs was 35.3%. Side effects of anti-hypertensive drugs was significant risk factor for non-adherence to anti-hypertensive drugs and common reasons for non-adherence were unwanted side effects (64.2%) followed by worry about long term side effects (62.3%). Conclusion: Prevalence of non-adherence to anti-hypertensive drugs was quite high, most common reason for non-adherence to anti-hypertensive medication was unwanted side effects and worry about long term side effects.